Efisiensi Modal Kerja Dan Profitabilitas Pada PT Semen Baturaja (Persero), Tbk Di Kabupaten Ogan Komering Ulu - Yuniarti Anwar; Yopi Yunsepa (STIE DWI SAKTI BATURAJA, 2019)
The purpose of this study was to determine the efficiency of working capital and profitability at PT Semen Baturaja (Persero), Tbk in Baturaja for the period 2013-2017. The method used in this study is the analysis of working capital efficiency ratio consisting of working turnover ratio, inventory turnover ratio, total asset turnover ratio and profitability ratio analysis consisting of from the ratio of gross profit margin (gross profit margin), the ratio of net profit (net profit margin), economic rentability ratio (basic earnings power, return on investment ratio and return on equity). The working capital efficiency ratio in the working capital turnover ratio always increases with an average ratio of 164,87%, while the inventory turnover ratio always decreases with an average ratio of 372,62% and total assets turnover ratio ( total asset turnover ratio) also always decreases with an average ratio of 38,97%. The profitability ratio in the gross profit margin ratio always increases with an average ratio of 51,07%, while the ratio of net profit (net profit margin) decreases with an average ratio of 21,72%, the ratio of economic profitability (basic earnings power) has decreased with an average ratio of 10,79% and the return on investment ratio (return on investment) has decreased with an average ratio of 8,48% and an equity return ratio (return on equity) also experienced decrease with an average ratio of 10,96%.